Time cube - Cai, Baolun (2010)
Urban city life is fast paced and saturated with the use of technology. Even in the midst of free time, there are people who remain in a restless state, moving quickly as they ‘forget’ to slow down. This perpetual state of restlessness creates a phenomenon that even when away from the workplace; in moments of rest, people are trying to fill up schedules with more and more activity. The Germans coin this term ‘freitzeitstress’, which literally mean ‘free time stress’. Stress that occurs during one’s free time is unusual and linked to stress and anxiety related issues. With the onslaught of fast living in urban society, stress and anxiety problems have risen to a point of ergomania(workaholism) and karoshi, or ‘death by work’ in Japanese. In view that one cannot stop time or people entirely, this project serves to find a solution to tackle the issue of ‘free time stress’ by occupying people and relieving them of ‘fastness’. With ‘time pass’ as a subject of interest, this project aims to capture the quality of passing time in a state that fulfills and satisfies.